(untitled) (Orthodontic Journal of Nepal, 2013)
A young lady presented to Department of Orthodontics with a chief complain of gap between upper and lower front teeth. On analysis she had Class I dental and skeletal malocclusion with proclined and forwardly placed incisors, and open bite. The treatment was carried out with extraction of all four first premolars and retraction was done with the help of mini-implant screws. Successful correction of open bite was achieved with “drawbridge effect”. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9286 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 69-72